Prognostic Factors for Locoregional Recurrence in Neuroendocrine Tumors of the Rectum. Issue 2 (February 2018) - Tsang, Erica S.; McConnell, Yarrow J.; Schaeffer, David F.; Yin, Yaling; Speers, Caroline H.; Kennecke, Hagen F.
Abstract : BACKGROUND: Optimal management of rectal neuroendocrine tumors is not yet well defined. Various pathologic factors, particularly tumor size, have been proposed as prognostic markers. OBJECTIVE: We characterized sequential patients diagnosed with rectal neuroendocrine tumors in a population-based setting to determine whether tumor size and other pathologic markers could be useful in guiding locoregional management. DESIGN: This study is a retrospective analysis of data from the British Columbia provincial cancer registry. SETTINGS: The study was conducted at a tertiary care center. PATIENTS: Sequential patients diagnosed with rectal neuroendocrine tumors between 1999 and 2011 were identified. Neuroendocrine tumors were classified as G1 and G2 tumors with a Ki-67 ⩽20% and/or mitotic count ⩽20 per high-power field. MAIN OUTCOME MEASURES: Baseline clinicopathologic data including TNM staging, depth of invasion, tumor size, treatment modalities, and outcomes including survival data were measured. RESULTS: Of 91 rectal neuroendocrine tumors, the median patient age was 58 years, and 35 were men. Median tumor size was 6 mm. Median length of follow-up was 58.1 months, with 3 patients presenting with stage IV disease. Treatment included local ablation (n = 5), local excision (n = 79), surgical resection (n = 4), and pelvic radiation (n = 1; T3N1 tumor). Final margin status was positive in 17 cases. Local relapse occurred in 8 cases and 1 relapse to bone 13 months after T3N1 tumor resection. Univariate analysis demonstrated an association between local relapse and Ki-67, mitotic count, grade, and lymphovascular invasion ( p < 0.01). Larger tumor size was associated with decreased disease-free survival. LIMITATIONS: Sample size was 91 patients in the whole provincial population over a 13-year time period because of the low incidence of rectal neuroendocrine tumors. CONCLUSIONS: In this population-based cohort, rectal neuroendocrine tumors generally presented with small, early tumors and were treated with local excision or surgical resection without pelvic radiation. Pathologic markers play a role in risk stratification and prognostication. SeeVideo Abstract athttp://links.lww.com/DCR/A514 .